Who, sir? Me, sir? - Peyton, K.M. (Oxford University Press, 2000)
Talks about Sam Sylvester, a teacher who wants his class to have ambition, and to do things in life. He enters them for a sporting competition against the rich students of Greycoats School. The team he has chosen think Sam is crazy. However, you never know what you can do - until you try